SEMANGAT BELAJAR MAHASISWA PADA MASA PANDEMI COVID-19 - St Ibrah Mustafa Kamal; Abdul Rahman; Mariyal Qibtiyah (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: The Spirit of Student Learning During The Covid-19 PandemicThis study aims to explain in detail how the objective conditions of student enthusiasm for learning are during the Covid-19 pandemic. The research was conducted at UIN Alauddin Makassar with a sample of 79 students. The data collection technique in this study uses a survey using a google form in order to reach students and uses a Likert scale in filling out the survey. The data analysis technique used in this study is to calculate the percentage of data from each indicator, then interpret the data presentation scores and analyze each indicator in depth. The results of this study indicate that the enthusiasm for learning of UIN Alauddin Makassar students is